Eco-friendly production of silver-copper nanoparticles using coconut husk and evaluation of its anti-cancer properties on human breast cancer (MDA-MB-231) cell line - Asiri, Atheer M.; Ali, Daoud; Al-Malahi, Nawal M.; Almarzoug, Mohammed H. A.; Almutairi, Bader O.; Alkahtani, Saad; Aldahmash, Badr A.; Alarifi, Saud (Frontiers in Molecular Biosciences, 2025)
The biological processes using green synthesis tool is safe, environmentally friendly, non-toxic, and economical, they are more suited to manufacturing nanoparticles with sizes between 1 and 100 nm than other related techniques. Here, I have used chemical methods to create bimetallic silver copper nanoparticles (Ag@CuNPs) utilizing coconut husk. Before exposure to target cells, the characterization of green silver copper nanoparticles (gAg@CuNPs) was done by UV vis spectrophotometer, scanning electron microscope (SEM), transmission electron microscopy (TEM), DLS. The shape of gAg@CuNPs are spherical and its size is measured 43.50 ± 1.5 nm. The cytotoxic effect of g Ag-Cu NPs on human breast cancer (MDA-MB-231) cells was determined by MTT and NRU tests. The cytotoxicity of gAg@CuNPs increased in a concentration-dependent manner and it showed high cytotoxic effect on MDA-MB-231 cells at the highest concentration of NPs exposure. From the MTT result I determined the median inhibitory concentration (IC50) for MDA-MB-231 cells at 24 h, which came out to be 66 μg/mL of NPs. Intracellular ROS levels was elevated at higher concentration of gAg@CuNPs. Superoxide dismutase (SOD) levels was increased at 33 μg/mL and it was reduced at 45 μg/mL. Glutathione (GSH) was reduced in MDA-MB-231 cells at high concentration of gAg@CuNPs. Using JC-1 staining, the loss of mitochondrial membrane potential in control, and gAg@CuNPs exposed cell were evaluated. In MDA-MB-231 cells, maximum apoptotic cells were observed at high concentration of NPs. Caspase-3/7 activity was increased in MDA-MB-231 cells at higher concentration of NPs. The above findings highlight the significance of gAg@CuNPs as cytotoxic agent brought on by oxidative stress, which frequently useful in a number of cancer treatments.